2021
DOI: 10.3906/sag-2001-79
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical and sonographic effects of ultrasound therapy, extracorporeal shock wave therapy, and Kinesio taping in lateral epicondylitis

Abstract: Comparison of the clinical and sonographic effects of ultrasound therapy, extracorporeal shock wave therapy and kinesio taping in lateral epicondylitis Abstract Background/aim: The aim of this study was to compare the clinical and sonographic effects of the ultrasound (US) therapy, extracorporeal shock wave therapy (ESWT), and Kinesio taping (KT) in the lateral epicondylitis (LE). Materials and methods: A total of 40 patients with LE were included in the present study. The patients were randomly assigned to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
0
20
0
4
Order By: Relevance
“…Some studies have reported the efficacy of US in LET treatment, but with low grade of study design and data, 40 and most of them focused on the comparison between US and ESWT. [41][42][43][44][45] Both Yalvaç B 43 and Özmen T 41 have shown significant improvements in pain, upper limb function, strength and quality of life from baseline after treatment with US. However, they did not have a control group, which would make it unclear whether the efficacy comes from US itself or the passing time, as LET is a self-limiting disease.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported the efficacy of US in LET treatment, but with low grade of study design and data, 40 and most of them focused on the comparison between US and ESWT. [41][42][43][44][45] Both Yalvaç B 43 and Özmen T 41 have shown significant improvements in pain, upper limb function, strength and quality of life from baseline after treatment with US. However, they did not have a control group, which would make it unclear whether the efficacy comes from US itself or the passing time, as LET is a self-limiting disease.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…As for tendinopathy, US is also a potential non-invasive treatment modality for frozen shoulder,34 35 rotator cuff,36 achilles37 38 and patellar39 tendinopathy. Some studies have reported the efficacy of US in LET treatment, but with low grade of study design and data,40 and most of them focused on the comparison between US and ESWT 41–45. Both Yalvaç B 43 and Özmen T 41 have shown significant improvements in pain, upper limb function, strength and quality of life from baseline after treatment with US.…”
Section: Introductionmentioning
confidence: 99%
“…В іншому РДК проаналізовано використання ЕУХТ (14 хворих) з УЗ і кінезіотейпуванням (13). За сонографічними дослідженнями виявлено більшу ефективність ЕУХТ [11], а порівняно з кінезіотейпуваннямменшу [12]. Лікувальний ефект від ЕУХТ був кращим у комбінації з нутритивною підтримкою [17].…”
Section: результати та їх обговоренняunclassified
“…К предрасполагающим факто рам можно отнести длительное пребывание за компью тером [10,11], работа с инструментами весом более 1 кг, а также создающими вибрацию [12][13][14], частый подъ ем груза весом более 20 кг, повторяющиеся движения в верхних конечностях более 2 часов в день, например у спортсменов [15][16][17]. Несмотря на устоявшееся назва ние «локоть теннисиста», ЛЭ характерен также для дру гих видов спорта, таких как баскетбол, легкая атлетика (метание диска, копья), бейсбол, сквош, бадминтон, бейсбол, плавание и другие [18][19][20][21]. Следует отметить, что из общего числа пациентов с ЛЭ только 5 % связы вают травму с большим теннисом [22].…”
unclassified
“…Как правило, ЛЭ хорошо поддается многим видам консервативного лечения. Но в некоторых случаях есть показания к оперативному вмешательству: сохране ние симптомов заболевания более полугода, несмотря на проводимую терапию [18]. На данный момент хирур гическое лечение ЛЭ недостаточно изучено: нет четкого определения удобных и безопасных доступов к локте вому суставу [12].…”
unclassified